2015
DOI: 10.1002/smll.201500491
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Sb/Sb2O3 Anode Materials Using a Polypyrrole Nanowire Network for Na‐Ion Batteries

Abstract: Three-dimensional porous Sb/Sb2 O3 anode materials are successfully fabricated using a simple electrodeposition method with a polypyrrole nanowire network. The Sb/Sb2 O3 -PPy electrode exhibits excellent cycle performance and outstanding rate capabilities; the charge capacity is sustained at 512.01 mAh g(-1) over 100 cycles, and 56.7% of the charge capacity at a current density of 66 mA g(-1) is retained at 3300 mA g(-1) . The improved electrochemical performance of the Sb/Sb2 O3 -PPy electrode is attributed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 32 publications
3
54
0
Order By: Relevance
“…Based on the combination of the XRD and TGA data, we speculate that an amorphous Sb/Sb 2 O 3 phase was formed during electrodeposition which converts to crystalline Sb 2 O 3 and NiSb (Ni is provided from Ni scaffold) during heat treatment. This speculation is consistent with previous reports which indicate that a mixture of Sb and Sb 2 O 3 is formed by electrodeposition from a potassium antimony tartrate electrolyte in the absence of HCl, while only Sb is deposited when the pH is reduced to 1.3 with HCl . In our system, acid was not added to the electrolyte.…”
Section: Resultssupporting
confidence: 93%
“…Based on the combination of the XRD and TGA data, we speculate that an amorphous Sb/Sb 2 O 3 phase was formed during electrodeposition which converts to crystalline Sb 2 O 3 and NiSb (Ni is provided from Ni scaffold) during heat treatment. This speculation is consistent with previous reports which indicate that a mixture of Sb and Sb 2 O 3 is formed by electrodeposition from a potassium antimony tartrate electrolyte in the absence of HCl, while only Sb is deposited when the pH is reduced to 1.3 with HCl . In our system, acid was not added to the electrolyte.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, it is found that the voltage gap of M‐Sb 2 S 3 @DC (0.65 V) is smaller than that of M‐Sb 2 S 3 (1.5 V) in Figure 4b, confirming its excellent reversibility during cycling. [ 24 ] Through the comparison of their charge–discharge potentials, note that those of M‐Sb 2 S 3 @DC are almost similar as exhibited in Figure S5 (Supporting Information), indicating its great cycling stability. For detailed exploring the effect of Sb‐C on the reaction process, the contribution ratios (CRs) of capacity for three redox procedures (including insertion, conversion, alloying) were shown in Figure 4e.…”
Section: Resultsmentioning
confidence: 79%
“…In the discharge/discharge platforms of Figure S5 (Supporting Information), it is found, those of M‐Sb 2 S 3 @DC were shown without much changes in comparison with those of M‐Sb 2 S 3 , demonstrating its reversibility of redox reactions at various density currents, while those of M‐Sb 2 S 3 have a serious fading. [ 26 ] As the current density increase, the rapidly diffused ions/e − in the electrolyte would be first deposited on the surface of electrodes without the reaction with active sites, finally giving rise to the steeply lowering of voltage. Benefitting from the establishing of SbC bonds as transferring bridges, the ions/e‐ would move through the carbon layer and outer space of metal‐sulfide, while diffusing into its interior, further rapidly reacting with the active sites.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative intercalation‐type anodes, such as Na 2 Ti 3 O 7 , Na 2 Ti 7 O 15 , or Na 2 Ti 6 O 13 , also exhibit capacities of less than 300 mAh g −1 . Alloy‐type anodes, such as Sn, Sb, Se, and P, could deliver much higher capacities for Na‐ion storage, which is however accompanied with extremely large volume change, resulting in formation of cracks, loss of electrical contact, and eventual collapse of electrode . Exploration of alternative high‐performance anode materials for NIB remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%